M(x+1)= 

ó õ 

M(y)dy+1; 




P  (  L(x+1) ³ h  )  = 

ó õ 

P  (  L(y) ³ h  )  P  (  L(xy) ³ h  )  dy. 
M(x+l) = 

ó õ 

(  M(y)+M(xy)+1  )  dy. 


=  ó õ 

(  1+(1l)  )  e 

exp 
æ ç ç ç ç è 
2  ó õ 


du 
ö ÷ ÷ ÷ ÷ ø 
dt. 
f(x+l,h) = 

ó õ 

f(xy, h)f(y,h) dy. 
P  (  H(n+1) £ h  )  = 


P  (  H(nm) £ h1  )  P  (  H(m) £ h1  )  . 
P  (  H (x+1) £ h  )  = 

ó õ 

P  (  H(xy) £ h1  )  P  (  H(y) £ h1  )  dy 



, 


, 
m_{i} (x,d) = 

ó õ 

( m_{i} (xy,d1)+m_{i} (y,d1)) dy. 
m_{i} (x,d) = 



, for 1 £ x, 
m_{i} (x,d) = 

e 

+O(1/d), 
m_{i} (x,d)= 2^{d}  

e 

+O(1/d), 

m_{e} (x,d)= 

m_{i} (x,d)= 


m_{e} (x,d)= 

{2^{d} m_{i} (x,d)}= 

This document was translated from L^{A}T_{E}X by H^{E}V^{E}A.